Certification, Verification and Governance in Forestry in Southeast Asia - World Bank (World Bank, Washington, DC, 2017)
The overall objective of the study is to explore the current effectiveness of certification and verification schemes in Southeast Asia to strengthen the legality and sustainability of future forest management, wood processing and related trade. It analyzes how the linkages among credible certification and verification schemes and the enforcement of forest laws can be strengthened in Southeast Asia. The analysis will in particular focus on five case study countries, which are important producer or wood processing hubs in the region: Indonesia, Lao PDR, Malaysia, Thailand and Vietnam. In particular, the study assesses the status and perceived credibility of certification and verification schemes in Southeast Asia and illustrates the extent to which they offer proof of compliance with national laws and regulations. The analysis also explores the potential impact certification could have on facilitating law enforcement and influencing market practices and sector governance. Finally, it illustrates the potential role certification could play in determining a company's qualifications with financial institutions and, hence, its access to finance.